Geomorphological and Anthropic Control of the Development of Some Adriatic Historical Towns (Italy) Since the Roman Age - Dall’Aglio, Pier Luigi; De Donatis, Mauro; Franceschelli, Carlotta; Guerra, Cristiano; Guerra, Veronica; Nesci, Olivia; Piacentini, Daniela; Savelli, Daniele (Quaestiones Geographicae, 2017)
The geomorphological analysis of historically urbanized areas is the best scientific way to understand how the extant geomorphological factors conditioned urbanization. It also provides a baseline to enable comparisons to be made with the modern environment. This paper considers four urbanized historical sites on the Adriatic coast (Italy) that owe their urban development to particular geomorphological and environmental conditions that were modified over the centuries from the Roman age to the present day. The focus here is on the evolution of the shoreline and associated geomorphic variables (streambeds and river mouths migration). These factors are fundamental for determining the development of a city, both as basic boundary elements – therefore including defence and protection – and also for the development of harbours.